Comparison of the Efficacy of Oxybutynin, Phenazopyridine, Celecoxib, and Placebo in the Treatment of Urinary Tract Symptoms after BCG Therapy in Patients with Bladder Tumors - Kamali, Koosha; Nikbakht, Javad; Ayubi, Erfan; Nabizadeh, Mostafa; Sarhadi, Saeedeh (Urology Journal, 2020)
Purpose: Intravesical BCG (Bacillus Calmette–Guérin) therapy is indicated as an effective treatment for patients with non-muscle-invasive bladder cancer, despite associate with the side effects. In this study, the incidence of BCG therapy adverse effects was compared among three groups of patients who received celecoxib, phenazopyridine, and oxybutynin with placebo. Materials and Methods: The randomized controlled clinical trial was conducted on four groups using the parallel group method. A checklist is used for weekly assessment of urinary symptoms, systemic symptoms of BCG therapy, and adverse drug reactions. Results: The study included 120 patients, 10 female and 110 male. The mean age 59.65 ± 6.2 years. The results of multivariate analysis show that there is a significant decrease in urinary frequency for patients who received phenazopyridine (95% CI: 0.09, 0.31, OR = 0.17, P <.001) and also celecoxib group (95% CI: 0.10, 0.43, OR = 0.21, P <.001) compared to those in placebo group. Patients in celecoxib group (95% CI: 0.02, 0.07 ,OR = 0.04, P <.001), phenazopyridine (95% CI : 0.07, 0.37,OR=0.16, P <.001) and oxybutynin (95% CI: 0.02, 0.12,OR = 0.05, P <.001) were less likely to have urgency than those in placebo. Moreover, significant decrease was found for dysuria in the three treatment groups in comparison with placebo group. Conclusion: According to the results, celecoxib, phenazopyridine and oxybutynin can effectively decrease the side effects of BCG immunotherapy compared to placebo. Among these three treatments, the most effective and safest treatment option is celecoxib.